[Temporarily Withdrawn] Oxidative stress in the pathogenesis of systemic lupus erythematosus - Shah, Dilip; Khanal, Puspa Raj; Sah, Sangita; Paudyal, Bishnuhari (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
This paper was temporarily withdrawn on 28th May 2014 due to a number of errors in the final version of the paper. DOI: http://dx.doi.org/10.3126/jmmihs.v1i2.9905 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(2) 2013; 26-37